Distal Bias of Meiotic Crossovers in Hexaploid Bread Wheat Reflects Spatio-Temporal Asymmetry of the Meiotic Program - Osman, Kim; Algopishi, Uthman; Higgins, James D.; Henderson, Ian R.; Edwards, Keith J.; Franklin, F. Chris H.; Sanchez-Moran, Eugenio (Frontiers in Plant Science, 2021)
Meiotic recombination generates genetic variation and provides physical links between homologous chromosomes (crossovers) essential for accurate segregation. In cereals the distribution of crossovers, cytologically evident as chiasmata, is biased towards the distal regions of chromosomes. This creates a bottleneck for plant breeders in the development of varieties with improved agronomic traits, as genes situated in the interstitial and centromere proximal regions of chromosomes rarely recombine. Recent advances in wheat genomics and genome engineering combined with well-developed wheat cytogenetics offer new opportunities to manipulate recombination and unlock genetic variation. As a basis for these investigations we have carried out a detailed analysis of meiotic progression in hexaploid wheat (Triticum aestivum) using immunolocalization of chromosome axis, synaptonemal complex and recombination proteins. 5-Bromo-2΄-deoxyuridine (BrdU) labelling was used to determine the chronology of key events in relation to DNA replication. Axis morphogenesis, synapsis and recombination initiation were found to be spatio-temporally coordinated, beginning in the gene-dense distal chromosomal regions and later occurring in the interstitial/proximal regions. Moreover, meiotic progression in the distal regions was coordinated with the conserved chromatin cycles that are a feature of meiosis. This mirroring of the chiasma bias was also evident in the distribution of the gene-associated histone marks, H3K4me3 and H3K27me3; the repeat-associated mark, H3K27me1; and H3K9me3. We believe that this study provides a cytogenetic framework for ongoing initiatives to manipulate recombination in the wheat genome.